СОВРЕМЕННЫЕ ПУТИ РАЗВИТИЯ ЦЕНТРОВ ОБРАБОТКИ НАУЧНЫХ ДАННЫХ - Исаев, Е. А.; Амзараков, М. Б.; Пугачев, В. Д; Самодуров, В. А.; Сухов, Р. Р.; Кобылка, Н. А. (Одеські астрономічні публікації, 2011)
In this paper shown, the development of modern datacenters (DC) for science and business. As an example of modern scientific datacenters used: buffer datacenter PRAO ASC LPI for the space project "Radioastron", compute cluster Pushchino Research Center (IMPB RAS) and Stack Data Network (SDN) – Russia’s first network of datacenters.